Digital Module Contains Traditional Balinese Games as an Effort to Improve Students' Mutual Cooperation Character - Rismayanti, Kadek Yuni; Antara, Putu Aditya; Trisna, Gusti Ayu Putu Sukma (MIMBAR PGSD Undiksha, 2024)
Teachers do not develop media as a tool in the learning process, there is a lack of use of technology and use of learning media, no media has been found that adopts traditional Balinese games, and the learning materials in students' books are still small and limited. The aim of this research is to develop digital modules for traditional Balinese games of digital modules for PPKN lesson content for class II elementary school students. The development model used in this research is the ADDIE model which has several stages, namely the analysis stage, design stage, development stage, implementation stage and evaluation stage. The subjects of research development are media experts, material experts, teachers and students, while the objects of development are validity and practicality. The data collection methods used were interview methods for research observation, rating scales and questionnaires to test the validity and practicality of the media. The results of the data analysis obtained are the validity results of media experts 4.6, material experts 4.4 and practicality level results (teachers and students) namely 5.00 so that digital modules are effective in improving the mutual cooperation character of class II students in PPKN subjects. Based on the average validity, user (teacher) response and effectiveness, the illustrated electronic module is suitable for use. With this digital module, it can facilitate students in the learning process so that students' cooperative character will increase optimally. This media can be developed and updated in further research to improve student achievement in learning.